A case study: exploring the impact of 3D printed models on cognitive integration during clinical skills training - Lisk, Kristina; Cheung, Jeffrey JH (Canadian Medical Education Journal, 2024)
Background: Cognitive integration occurs when trainees make conceptual connections between relevant knowledges and is known to improve learning. While several experimental studies have demonstrated how text and audio-visual instruction can be designed to enhance cognitive integration, clinical skills training in real-world contexts may require alternative educational strategies. Introducing three-dimensional (3D) printed models during clinical skills instruction may offer unique learning opportunities to support cognitive integration. Methods: Using case study methodology, we explore how learners and an instructor used 3D printed bones to augment their learning interactions during a clinical skills laboratory on shoulder on palpation, and to describe the instructional strategies with 3D printed bones that may support learning. Students (n = 21) worked in small groups and were given access to a 3D printed clavicle, scapula, and humerus. Data were collected through observation, a student focus group, and a semi-structured interview with the instructor. Thematic analysis to review and code the data and to generate themes. Results: We developed four themes that describe how 3D printed models were used in the classroom and how they may support cognitive integration: classroom interactivity, visualization of anatomy, integrating knowledge, and educational potential. Conclusions: The findings demonstrate several ways 3D printed models can augment how learners, instructors, and educational materials interact with one another and how readily learners make connections between different sources and types of knowledge. This research extends previous work by demonstrating how social learning processes and interactions with physical models can offer unique affordances that may support cognitive integration.